ANALISA DAN PENGEMBANGAN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU PADA STMIK PRABUMULIH - iwan setiawan (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2022)
Technological developments in today's increasingly sophisticated era can also provide ideas for finding alternatives in accessing the internet without having to go through a computer. From this idea finally emerged various kinds of electronic products that can be used to access the internet. The progress of science and technology plays a very important role in every activity, be it companies, industries, government agencies and educational institutions. So from the explanation above here the author wants to make an information media tool that analyzes and develops new student admissions information systems at STMIK Prabumulih, with using the waterfall method, with stages, software requirements analysis, design, programming coding, testing, supporting UML design models supporting design tools, namely use cases, activity diagrams, class diagrams, the programming language used is PHP and MySQL database, of course with the existence of This system will make it easier to convey various information as well as job information or other forms of information and to add an accreditation value at a high school.